Cloud Kitchen Development Analysis in Food and Beverage Industry: A Case Study in Jakarta - Susilowati, Etty; Yuwono, Avatar Akbar; Leonnard, Leonnard (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to analyze the development of the concept of "Cloud Kitchen" or "Dark Kitchen" or "Virtual Kitchen" in DKI Jakarta. In addition, exploration of each brand is carried out so that the potential of each brand can be seen. Empowerment of Micro, Small and Medium Enterprises (MSMEs) also needs to be considered as one of the motives for cooperation in the concept of "Cloud Kitchen" or "Dark Kitchen" or "Virtual Kitchen" in DKI Jakarta. Actually, the concept of cloud kitchen is not a new thing in DKI Jakarta and its surroundings. Currently, in DKI Jakarta there are at least 7 cloud kitchen players, namely Dapur Bersama GoFood, GrabFood Kitchen, Everplate, Yummykitchen, Kita Kitchen, Telepot, and Eatsii. In the Stars position, the GoFood and Yummykitchen Joint Kitchens are in that quadrant. Meanwhile, in the Question Marks position, there are GrabFood Kitchen, Everplate, Kita Kitchen and Telepot. However, for Eatsii it is still difficult to map considering that it has just established since 2021. The development strategies of these players are varied, one of which is the effort to support the empowerment of MSMEs in DKI Jakarta. The large potential of MSMEs in DKI Jakarta is a strategy for cloud kitchen players to increase their market share and growth potential. However, considering that this research is still qualitative and on desk research, further research is needed.